KAJIAN SOSIAL EKONOMI PETANI KOPI ARABIKA KELURAHAN AGUNG LAWANGAN KECAMATAN DEMPO UTARA KOTA PAGAR ALAM - iswarini, Harniatun; Afriyatna, Sisvaberti; Ardina Ningrum, Puri Pratami; Apriani, Novi; Habibi, Nur I.E. (AGRIBIOS, 2025)
The purpose of this study is to examine the socioeconomic status of the Arabika coffee industry in Agung Lawangan district in Pagaralam city. This research is a study cualitative that uses purposive sampling. Data is gathered by observation. The results of the social and economic analysis of education indicate that the average of education for coffe farmer arabika education farmer has the ability to understand complex information such as the price of kopi arabika, government subsidy programs, technical assistance, and follow in the classroom to increase production, reduce risk, and minimize losses due to fluctuations in prices, bad weather, or other pest. Family Responsibillity coffe farmer arabika has five people, as well as the responsibillity in the largest category, can be used to reduce the dependence worker from the outside family activities. It is possible to reduce the cost of labor and maybe increase earnings. Arabica coffee farmer working hours varies since only two petani do not have sampingan usahatani, while five other respondents, in addition to focusing on arabica coffe, also devoted time to farming and the others. On the other hand, income In Kelurahan Agung Lawangan, in Pagaralam city arabica farmer is included in the category of mid. Income If the minimum wage regional (UMR) value in Pagaralam city is Rp 3.456.874, then the farmer coffe arabica pay is higher than that of Palembang minimum wage (UMP) Pagralam city, and it can be said that it has better access to public services like health and education